Effects of intellectual capital and ownership structure on financial outcomes and distribution dynamics in Indonesian State-Owned Enterprises (SOEs) - Rachmawati, Rima; Lubis, Mukhlis (Kasetsart Journal of Social Sciences, 2026)
This study investigates the impact of intellectual capital disclosure and the distribution of its components. Components of intellectual capital in this study include human capital, structured capital, correlated capital, and employed capital skills. This study examines the impact of intellectual capital and structural ownership on financial performance, measuring financial performance using asset returns. The study investigated the distributive effects of intellectual capital by analyzing panel data from Indonesia’s state owned enterprises (SOEs) over the five years from 2018 to 2022. A modified intellectual capital value-added coefficient model is applied to examine the distributive effects of intellectual capital (IC) skills on financial performance. Empirical findings indicate that IC competence, human capital efficiency, structured capital efficiency, employed capital efficiency, and relational capital skills are positively and significantly related to financial performance in the distribution. However, the distribution of physical and structural capital is the most important component of profit-generating intellectual capital skills. The distribution of public and foreign ownership positively affects financial performance. This research will help managers, policymakers, and investors decide how the distribution of IC investments enhances performance and makes informed investment decisions in public and foreign-owned companies.